Populism and the liberal international order: An analysis of UN voting patterns - Sandra Destradi; Johannes Vüllers (The Review of International Organizations, 2024)
Populism is often assumed to undermine the liberal world order, but this claim has never been tested systematically. In this study, we do so for the first time. Based on an understanding of populism as a “thin-centered ideology” entailing anti-elitism and people-centrism, we expect populist governments to have foreign policy preferences opposed to the core features of the US-led liberal international order. Our empirical analysis assesses government preferences on the liberal international order as expressed through UN General Assembly votes. Our findings support the expectation that populism has a strong and statistically significant negative impact on foreign policy preferences related to the core norms of the liberal international order. Moreover, we find that populists with a left-wing ideology and those in less democratic countries tend to be more opposed to the US-led liberal international order. However, populist governments do not reject the UNGA as such, as they are not more likely to be absent from UNGA votes than other states. Thereby, this study makes a contribution both to the burgeoning literature on the international implications of populism and to debates on the crisis of the liberal order.
Keywords: F50; F53; F55; 320; Populism; United Nations; UNGA voting patterns; Liberal international order; International impact of populism